What You See Is What You Get? Exclusion Performances in Ravens and Keas - Schloegl, Christian; Dierks, Anneke; Gajdon, Gyula K.; Huber, Ludwig; Kotrschal, Kurt; Bugnyar, Thomas (PLOS ONE, 2009)
Background Among birds, corvids and parrots are prime candidates for advanced cognitive abilities. Still, hardly anything is known about cognitive similarities and dissimilarities between them. Recently, exclusion has gained increasing interest in comparative cognition. To select the correct option in an exclusion task, one option has to be rejected (or excluded) and the correct option may be inferred, which raises the possibility that causal understanding is involved. However, little is yet known about its evolutionary history, as only few species, and mainly mammals, have been studied. Methodology/Principal Findings We tested ravens and keas in a choice task requiring the search for food in two differently shaped tubes. We provided the birds with partial information about the content of one of the two tubes and asked whether they could use this information to infer the location of the hidden food and adjust their searching behaviour accordingly. Additionally, this setup allowed us to investigate whether the birds would appreciate the impact of the shape of the tubes on the visibility of food. The keas chose the baited tube more often than the ravens. However, the ravens applied the more efficient strategy, choosing by exclusion more frequently than the keas. An additional experiment confirmed this, indicating that ravens and keas either differ in their cognitive skills or that they apply them differently. Conclusion To our knowledge, this is the first study to demonstrate that corvids and parrots may perform differently in cognitive tasks, highlighting the potential impact of different selection pressures on the cognitive evolution of these large-brained birds.